The Use of Youtube Media In Enhancing Vocabulary Mastery of Eleventh Grade Students at SMKN 1 Gowa - St. Nurhikma; Syarifuddin Dollah; Samtidar (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2026)
This study investigates students’ perceptions of YouTube as a medium for learning English vocabulary among eleventh-grade vocational school students. With the growing use of digital platforms in language education, understanding how learners evaluate the effectiveness of such tools is increasingly important, particularly in supporting vocabulary development. Employing a qualitative descriptive approach, data were collected through classroom observations and semi-structured interviews with six purposively selected students. The findings indicate that students hold highly positive perceptions of YouTube, viewing it as an enjoyable, flexible, and supportive platform that provides contextualized audiovisual input for vocabulary learning. Features such as subtitles, replay options, and diverse content were perceived to facilitate comprehension, repeated exposure, and retention of new words, while also enhancing motivation and confidence. Challenges such as fast speech and pronunciation differences were noted but were generally manageable through repeated viewing and teacher guidance. Overall, the study concludes that YouTube serves as an effective complementary tool for vocabulary learning and has potential to strengthen more innovative, student-centered instructional practices.